Seasonal plasticity of the polar lipidome of Ulva rigida cultivated in a sustainable integrated multi-trophic aquaculture - Moreira, Ana S. P. (2020)
Green macroalgae of the genus Ulva, commonly known as sea lettuces, are currently traded worldwide for multiple applications, including human consumption. In this work, we evaluated the seasonal variation of the total content of lipids, esterified fatty acids (FAs) and polar lipids (the major carriers of FAs) at the level of the classes and molecular species of Ulva rigida cultivated in Portugal in a land-based integrated multitrophic aquaculture (IMTA) system. Comparing winter, spring, summer and autumn samples, the lipid content and abundance of unsaturated FAs, namely n-3 polyunsaturated FAs, were highest in winter and lowest in summer. However, regardless of seasonal variations, U. rigida had a low n-6/n-3 ratio in all seasons, which is associated with health benefits. Among the polar lipids, those that varied the most were betaines, glycolipids and phospholipids, including a high number of lysolipid species that increased during autumn and spring. Multivariate analysis using principal component analysis (PCA) showed better discrimination of the four seasons when the dataset on molecular lipid species was used. Knowledge of the seasonal variability of lipid composition in biomass of Ulva rigida can be used to better explore these green macroalgae as a source of bioactive polar lipids with high market value.